Production and commercialization of benzoin resin: Exploring the value of benzoin resin for local livelihoods in North Sumatra, Indonesia - Harada, Kazuhiro (Elsevier B.V., 2022)
Non-timber forest products (NTFPs) are a source of income for local communities. This study aims to clarify the customary management system adopted in benzoin tree cultivation as well as analyze the significance of retaining customary management practices in North Sumatra, Indonesia. Local people customarily harvested sap in benzoin forests that they inherited from their ancestors. The resin had a strong market chain moving from domestic to international markets via village middlemen and traders in the sub-districts and districts, and contributed to their income generation. Even with the introduction of commercial crops as coffee in the 1990s, resin production from benzoin trees with intensive labor was continued. The village had strict rules on not selling benzoin forests to others. It is concluded that, in addition to serving as a source of income for local people, the locals had a strong sense of responsibility to continue to manage benzoin forests as inherited custom and protect the benzoin forests. © 2021 The Author(s)